DIFFERENCES OF HEAD FORM CHARACTERISTICS USING CHEPALIC INDEX ON KALIMANTAN TRADE (Identification Study of Male and Female Head Shape In Dayak Ngaju tribe, Dayak Bukit tribe and Banjar Hulu tribe) - Siti Mona Herliani U; Irnamanda DH; Iwan Aflanie (FKG Unlam, 2018)
Background: The island of Borneo is inhabited by various tribes such as Dayak Ngaju tribe, Dayak Bukit tribe and Banjar Hulu tribe. According to Radam (1987) the Dayak Bukit and Banjar Hulu tribes have the closest kinship, while the theory of Tjilik Riwut (1979) says Dayak Bukit tribe is part of Dayak Ngaju tribe. The difference between the two theories is still debatable so it needs to be identified. Identification of all three groups is by using the chepalic index. Objective: To find out the average head width, head length and chepalic index between men and women in the three groups of tribes in Kalimantan. Method: This study was an observational analytic study with cross sectional design, using respondents of 180 people consisting of 60 people in each tribe groups. Characteristic of head shape was measured by using chepalic index. Results: Research data were analyzed using Kruskal Wallis test. The Kruskall Wallis test of head width, head length and chepalic index yielded p = 0,000 (p <0.05). It showed significant differences in head width, head length and chepalic index between the three ethnic groups in Kalimantan, while the chepalic index of the three tribes produced p > 0,05 which showed no difference in mean value of chepalic index between male and female in all three groups. Conclusion: Based on the comparison of head width, head length and chepalic index, it can be concluded that there is a possibility of kinship relationship between Dayak Bukit tribe and Banjar Hulu tribe.